Does soaking temperature during controlled slow freezing of pre-pubertal mouse testes influence course of in vitro spermatogenesis? - Arkoun, Brahim; Dumont, Ludovic; Milazzo, Jean-Pierre; Rondanino, Christine; Bironneau, Amandine; Wils, Julien; Rives, Nathalie (Cell and tissue research, 2016)
The banking of testicular tissue before highly gonadotoxic treatment is a prerequisite for the preservation of fertility in pre-pubertal boys not yet producing sperm. The aim of the current study is to evaluate the impact of a soaking temperature performed at −7 °C, −8 °C or −9 °C on the ability of frozen-thawed mouse spermatogonial stem cells (SSCs) to generate haploid germ cells after in vitro maturation. Testes of 6.5-day-old post-partum CD-1 mice were cryopreserved by using a controlled slow freezing protocol with soaking at −7 °C, −8 °C or −9 °C. Frozen-thawed pre-pubertal testicular tissues were cultured in vitro on agarose gel for 30 days. Histological evaluations were performed and flagellated late spermatids were counted after mechanical dissection of the cultured tissues. The differentiation of frozen SSCs into elongated spermatids was more efficient after treatment at −9 °C than at −7 °C and −8 °C. After dissection, flagellated late spermatids were observed by using Shorr staining. The number of flagellated late spermatids was significantly decreased after slow freezing when compared with a fresh tissue control. Therefore, the soaking temperature during slow freezing of pre-pubertal mouse testicular tissue might positively influence the course of in vitro spermatogenesis. Our slow freezing protocol with a soaking temperature at −9 °C was the optimal condition in terms of the achievement of in vitro spermatogenesis with a higher production of elongated spermatids, although the effectiveness of the maturation process was reduced compared with the fresh tissue control.